Early Exposure to Gut Microbiome Reduces Hepatocellular Carcinoma Risks in Mice. (16th March 2020) - Lee, Yang-Ming; Chang, Wei-Chun; Lei, Fu-Ju; Kor, Chew-Teng; Lai, Hsueh-Chou; Chen, Yao-Li; Ma, Wen-Lung
Abstract : Aims . Liver cancer is a multietiological disease that has multiple factors contributing to the hepatocarcinogenic process, e.g., hepatitis viruses, carcinogens, male sex, or metabolic factors. Notably, emerging evidence reported that gut microbiota is crucial to the pathogenesis of hepatocellular carcinoma (HCC) via activation of innate immunity. However, the effect of time to gut microbiota exposure after birth is unknown. Using a germ-free animal housing environment, instead of antibiotics, we examined the effects of various time-to-exposure (TTE) to gut microbiota durations on HCC risk. Methods . HBV or carcinogen-mediated spontaneous HCC models were implemented in this study. The HCC incidence rates in mice either kept germ-free (GF; that is, with no exposure to gut microbiota) or exposed to gut microbiota after being moved to a specific pathogen-free (SPF) housing environment and with various time-to-exposure (TTE) durations, namely, 5 weeks after birth, 10 weeks after birth, or since conception (that is, 5-week TTE group, 10-week TTE group, and SPF group, respectively), were recorded. The mice were sacrificed at 30 or 40 weeks after birth, and macro-/microscopic observations and pathological diagnosis were performed. Results . The incidence of liver tumors among the male mice was higher than that among the female mice in the carcinogen-induced HCC mice sacrificed at 40 weeks after birth (with P = 0.011, 0.035, 0.0003, and 0.012, respectively, in the GF group, 5-week TTE group, 10-week TTE group, and SPF group). Similarly, in the HBV-HCC model, the incidence of liver tumors among the male mice was significantly higher than that among the female mice (with P = 0.013, 0.020, 0.012, and 0.002, respectively, in the GF group, 5-week TTE group, 10-week TTE group, and SPF group). These results suggest that gut microbiota exposure is irrelevant to the male sex preference of HCC. Surprisingly, when comparing carcinogen-induced HCC male mice in the 10-week TTE group (90%; n = 10 ), 5-week TTE group (56%; n = 9 ), and SPF group (30%; n = 10 ) (P = 0.020 ), we found that the incidence of liver tumors was higher in the mice with later exposure to gut microbiome. Similarly, when comparing HBV-HCC male mice in the 10-week TTE group (100%; n = 11 ), 5-week TTE group (70%; n = 10 ), and SPF group (33%; n = 9 ) (P = 0.080 ), we also found that the incidence of liver tumors was higher in the mice with later exposure to gut microbiome. Conclusions . Early (prepubertal) exposure to gut microbiome reduces the risk of HCC development, indicating a potentially important factor for cancer surveillance. Exploring the mechanisms by which such exposure affects HCC risk might lead to novel cancer vaccines.